Mechanical performance of non-reinforced, carbon fiber reinforced and glass bubbles reinforced 3D printed PA12 polyamide. (15th January 2023) - Pejkowski, Łukasz; Seyda, Jan; Nowicki, Krzysztof; Mrozik, Dariusz
Abstract: Reinforcing the materials used in 3D printing with different fillers like short and continuous fibers or micro and nanoparticles is a common way of increasing their mechanical properties. In real applications, parts manufactured from reinforced polymers may be exposed to loadings of various rates. However, there is relatively little data on the rate-depended behavior of 3D printed materials and components available in the literature. The present study aims to provide some basic information about the mechanical behavior of PA12 polyamide and its composites manufactured by filament deposition technology. 3D printed specimens were tested under the monotonic tensile loading of various strain rates and subjected to creep and creep recovery tests. The results showed an important strain rate effect in the case of all tested materials. Reinforced materials exhibited improved mechanical properties. The highest tensile strength and creep resistance were achieved for the carbon fiber reinforced material, in the case of which the damage mechanism consisted of carbon fibers breaking before pulling out from the polymer matrix. Graphical abstract: Image 1 Highlights: Mechanical performance of 3D printed PA12 polyamide and its composites was tested. Composites included glass bubbles reinforced and carbon fibers reinforced filaments. Strain rate-dependent behavior of materials was investigated. Monotonic tension test at various strain rates were conducted. Long-term behavior was tested in creep and creep-recovery tests.